Assessment of Potentiality of Ecotourism in Sri Lankan Context: An Analytical Study of Econometric Basis - Vijayakumar, S.; Nisthar, S.; Nufile, A.A.M. (Faculty of Arts and Culture South Eastern University of Sri Lanka, 2016)
This study aimed to statistically measure the potentiality of resources of Ecotourism on Gross Domestic Product of Sri Lanka and to direct the policy makers to appropriately identify the resources of ecotourism contributing to Gross Domestic Product of Sri Lanka. The data used in this study were collected from Sri Lanka Tourism Development Authority and Annual Report of Central Bank of Sri Lanka from the period of 1983 to 2013. The variables used in this study were CTR, ZGR, BGR, BMICHR, WPR, ETR and RGDP. CTR, ZGR, BGR, BMICHR, WPR, and ETR were used in this study as the independent variables. RGDP is used as the dependent variable in this study. The quantitative methodology used in this study was based on the econometric analysis using the Statistical Software of E-Views, Minitab and MS Excel in collaboration with the parametric analyses. The time series econometric techniques such as Augmented Dickey Fuller (ADF) for unit root test, Johnson co-integration test for the long run relationship, Granger causality test for causal relationships between the variables and Residual test for best regression model were used in this study. There was a positive relationship between BGR, BMICHR, CTR, ETR and RGDP and an inverse relationship was found between RGDP, WPR and ZGR. The value of R-squared was 0.9637 and Durbin Watson statistic was 0.6365. The residual was stationary along with all the other variables. The Granger causality test showed the different way causal relationships between all the variables. This study prominently suggested for the government and policy makers to keep on focusing on the economic policies to be designed for the promotion of ecotourism industry as one of the prospective sources for economic growth and development in Sri Lanka. Keywords: Ecotourism, Gross Domestic Product, Cointegration, Spuriousness, Stationary
Keywords: Ecotourism; Gross Domestic Product; Cointegration; Spuriousness; Stationary